2004
DOI: 10.21273/hortsci.39.4.841a
|View full text |Cite
|
Sign up to set email alerts
|

Temperate Fuits Production in the Tropics: A Review on Apples in Kenya

Abstract: Temperate zone fruit crops undergo bud dormancy which can be described as a mechanism for avoiding the exposure of tender flowers and leaves to low winter temperatures. In Kenya, apple growing is mostly hampered by inadequate chilling that causes the plants to have prolonged dormancy leading to poor flowering and consequently low yield. Although the chilling requirements are obligatory, under subtropical and especially tropical conditions avoidance is possible. To achieve this, it is necessary to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Deciduous trees require exposure to low winter temperatures is called a chilling requirement to overcome dormancy and grow in the following spring (Howe et al, 1999 andArora et al, 2003). Also, Njuguna et al (2004) reported that, temperate zone fruit crops undergo bud dormancy which can be described as a mechanism for avoiding the exposure of tender flowers and leaves to low winter temperatures. The induction of dormancy occurs in response to seasonal environmental signals.…”
Section: Introductionmentioning
confidence: 99%
“…Deciduous trees require exposure to low winter temperatures is called a chilling requirement to overcome dormancy and grow in the following spring (Howe et al, 1999 andArora et al, 2003). Also, Njuguna et al (2004) reported that, temperate zone fruit crops undergo bud dormancy which can be described as a mechanism for avoiding the exposure of tender flowers and leaves to low winter temperatures. The induction of dormancy occurs in response to seasonal environmental signals.…”
Section: Introductionmentioning
confidence: 99%
“…Temperate zone fruit crops bear bud dormancy which may be represented as a mechanism for avoiding the exposure of tender flowers and leaves to low winter temperatures (Njuguna et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Warm winters result in prolonged dormancy leading to poor flowering, very strong apical dominance, unsynchronized growth patterns and, consequently, low yields (Cook and Jacobs, 2000;Jacobs et al, 1981). Apple growing is commonly hampered by inadequate winter chilling in Kenya (Njuguna et al, 2004) and Moroccan valleys (Mahhou et al, 2003). One of the possible solutions to avoid such problems is using low chilling requirement cultivars such as Anna (Erez, 2000;Njuguna et al, 2004;Webster, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Apple growing is commonly hampered by inadequate winter chilling in Kenya (Njuguna et al, 2004) and Moroccan valleys (Mahhou et al, 2003). One of the possible solutions to avoid such problems is using low chilling requirement cultivars such as Anna (Erez, 2000;Njuguna et al, 2004;Webster, 2005). However, these cultivars do not always meet the demands of growers and consumers with respect to production volume and fruit quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation